PENGARUH CREATIVE RESPONSIBILITY BASED LEARNING MODEL TERHADAP KOMPETENSI KETERAMPILAN SISWA PADA MATA PELAJARAN KECANTIKAN DASAR DITINJAU DARI MOTIVASI BELAJAR - Syafitri, Yustina; Basuki, Ismet; Handajani, Sri (Academy of Education Journal, 2023)
Determining success in education, students must be ready to face the times that are happening at this time. This study aims to determine how the effect of Creative Responsibility-Based Learning Model on students' skills in Basic Beauty Subjects suggested from learning motivation. This type of research is a quantitative research that is quasi-experimental with a 2x2 factorial design. Research instruments in the form of performance tests, observations. The research sample was students of SMK 1 Buduran Sidoarjo as the experimental class which applied the CRLBM learning model and students of SMK 1 Sooko Mojokerto as the control class which used the MPL learning model. The results showed that there were differences in the competence of the skills domain between students who were taught using CRBLM, students who were taught using MPL in beauty subjects. There is a difference in competence in the skills domain between students who have high learning motivation and students who have low learning motivation in basic beauty subjects. There is an interaction between the learning model and students' learning motivation on the competence of the skill domain with an F value of the skill domain of 54,269 in the basic beauty subject. Research Implications The application of the CRBLM learning model supported by the right media will motivate students to receive material so that motivation will affect students' competence in the realm of knowledge, attitudes and skills.